Operational risk in Icelandic tourism companies - Sólveig Maria Seibitz 1993- (2018)
In this study operational risk management in Icelandic tourism companies is examined. Tourism has become an increasingly important industry in Iceland and there are now more companies operating in the industry than ever before. Therefore, the aim of this study is to investigate, which tools are being used throughout the risk management process, to explore which strategies are being used to reduce risk and to examine which risks companies deemed important. This study also explores if certain company characteristics affect a company’s risk management. A survey is sent to Icelandic tourism companies operating in the accommodation, travel agency and car rental sub industries, which are sub industries who are totally reliant on tourists. The survey is answered by 48 companies and the findings show that most companies are using some form of risk management, however not all companies are using methods for each step in the risk management process. Companies deemed external risks to be most important which include environmental, political and competition. Size of a company is found to be an indicator of how sophisticated a company’s risk management approach is while age and profitability are not. A recommendation for companies working in the Icelandic tourism industry would be to follow through with the risk management process and to address each step starting with identifying relevant risks, evaluating those risks, selecting strategies to mitigate them and finally monitoring the risks which may include revising the risk management strategy accordingly.